Feedlot performance, rumen and cecum morphometrics of Nellore cattle fed increasing levels of diet starch containing a blend of essential oils and amylase or monensin - Silva, Thaiano I. S.; Souza, Johnny M.; Acedo, Tiago S.; Carvalho, Victor V.; Perdigão, Alexandre; Silva, Leandro A. F.; Silvestre, Antonio M.; Niehues, Maria Betania; Schleifer, Werner F.; Casali, Daniel M.; Martins, Cyntia L.; Arrigoni, Mario D. B.; et al. (Frontiers in Veterinary Science, 2023)
Feed additives used in finishing diets improve energy efficiency in ruminal fermentation, resulting in increased animal performance. However, there is no report evaluating the effect of BEO associated with exogenous α-amylase in response to increased starch content in feedlot diets. Our objective was to evaluate increasing levels of starch in the diet associated with a blend of essential oils plus amylase or sodium Monensin on performance, carcass characteristics, and ruminal and cecal morphometry of feedlot cattle. 210 Nellore bulls were used (initial body weight of 375+13.25), where they were blocked and randomly allocated in 30 pens. The experiment was designed in completely randomized blocks in a 3x2 factorial arrangement: three starch levels (25, 35, and 45%), and two additives: a blend of essential oils plus α-amylase (BEO, 90 mg/kg and 560 mg/kg of DM, respectively) or sodium Monensin (MON, 26 mg/kg DM). The animals were fed once a day at 08:00 ad libitum and underwent an adaptation period of 14 days. The diets consisted of sugarcane bagasse, ground corn, soybean hulls, cottonseed, soybean meal, mineral-vitamin core, and additives. The animals fed BEO35 had higher dry matter intake (P= 0.02) and daily weight gain (P= 0.02). The MON treatment improved feed efficiency (P= 0.02). The treatments BEO35 and BEO45 increased hot carcass weight (P< 0.01). Animals fed BEO presented greater carcass yield (P= 0.01), carcass gain (P< 0.01), rib eye area gain (P= 0.01), and final rib eye area (P= 0.02) when compared to MON. The MON25 treatment improved carcass gain efficiency (P= 0.01), final marbling (P= 0.04), and final subcutaneous fat thickness (P< 0.01). The use of MON reduced the fecal starch% (P< 0.01). Cattle-fed BEO increased rumen absorptive surface area (P= 0.05) and % ASA papilla area (P< 0.01). The MON treatment reduced the cecum lesions score (P= 0.02). Therefore, the use of BEO with 35 and 45% starch increases carcass production with similar biological efficiency as MON; and animals consuming MON25 improve feed efficiency and reduce lesions in the rumen and cecum.